Next-generation lead-free solar cells with MASnBr3/ZnSnN2 dual absorbers for high efficiency - Md. Mehedi Hasan; Mst. Aysha Siddika; Md. Feroz Ali; Md. Rafiqul Islam Sheikh; Abdullah Al Mamun; Abdullah Al Mamun; Md Jakir Hossen (Frontiers in Materials)
This study presents a next-generation lead-free perovskite solar cell (PVSC) architecture employing a dual-absorber design using MASnBr3 and ZnSnN2 to enhance photovoltaic performance while ensuring environmental sustainability. The proposed structure—FTO/n-ZnO/p-MASnBr3/p-+ZnSnN2/p-++CNTS/Au—was simulated and optimized using SCAPS-1D software. Extensive material and structural optimization was conducted, including selection of electron and hole transport layers as well as tuning absorber thickness, doping concentration, and defect density. The dual-absorber configuration leverages the complementary optical properties of MASnBr3 (bandgap: 1.3 eV) and ZnSnN2 (bandgap: 1.5 eV), enhancing spectral absorption and carrier separation. Optimization of interface properties, series/shunt resistance, and operating temperature further improved the device’s efficiency and stability. The final optimized structure achieved a power conversion efficiency (PCE) of 35.87%, with open-circuit voltage (VOC) of 1.17 V, short-circuit current density (JSC) of 34.39 mA/cm2, and fill factor (FF) of 89.01%. Quantum efficiency analysis confirmed near-unity photon-to-charge conversion across the visible spectrum. This work demonstrates the viability of combining lead-free perovskites with nitride absorbers for high-efficiency, eco-friendly solar technologies and provides a scalable pathway for future experimental validation and commercialization of sustainable photovoltaic systems.